Searching for a question and an answer - Le Roux, J (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
This article focusses on Eckart Otto’s theory of the Pentateuch, his contribution to Pro Pent (the “Project for the study of the Pentateuch”) and his influence on our understanding of the first five books of the Hebrew Bible. There was something in his thinking that appealed to many South African scholars; an appeal that softened down the harsh criticism and blunted the sharp edges of Pentateuch study of the past two centuries. And this was accomplished by turning the focus to the theological and ethical issues, which were the driving forces behind the formation of the Pentateuch. Put differently: to show the Pentateuch as an answer to a question and Pentateuch criticism as a constant search for the questions to which the Pentateuch is answer.